2009
DOI: 10.1309/ajcp3cx3auvrbhcf
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Level of Growth Arrest–Specific 6 (GAS6) Protein and Genetic Variations in the GAS6 Gene in Patients With Acute Coronary Syndrome

Abstract: Growth arrest-specific gene 6 (GAS6) encodes a vitamin K-dependent protein that regulates inflammation, angiogenesis, and atherosclerotic plaque formation. The level of GAS6 expression is associated with plaque stability and stroke. We explored the role of GAS6 in cardiovascular disease, particularly in acute coronary syndrome (ACS). We determined the plasma levels of GAS6 protein by using an enzyme-linked immunosorbent assay method and investigated the role of the single nucleotide polymorphism (c.834+7G>A) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 16 publications
2
43
3
Order By: Relevance
“…Superior to other biomarkers, like sRAGE and vWF, Gas6, with the peculiar and newly-discovered ability, can deepen the understanding on the pathogenesis of ALI in an early stage. Literatures have reported the credible effect of Gas6 as a biomarker in diagnosis of acute coronary syndrome (ACS) (Jiang et al 2009), and the association between the Gas6 and various diseases, such as sepsis (Ekman et al 2010). The results of this study showed that Gas6 could be used to predict the development of ALI, suggesting that innate immune response is the first mechanism in response to injuries to patients at an early-stage ALI (Nassar et al 2017).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Superior to other biomarkers, like sRAGE and vWF, Gas6, with the peculiar and newly-discovered ability, can deepen the understanding on the pathogenesis of ALI in an early stage. Literatures have reported the credible effect of Gas6 as a biomarker in diagnosis of acute coronary syndrome (ACS) (Jiang et al 2009), and the association between the Gas6 and various diseases, such as sepsis (Ekman et al 2010). The results of this study showed that Gas6 could be used to predict the development of ALI, suggesting that innate immune response is the first mechanism in response to injuries to patients at an early-stage ALI (Nassar et al 2017).…”
Section: Discussionmentioning
confidence: 71%
“…(Happonen and Dahlback 2016. Gas6 is associated with cardiovascular disease (CVD) and provides further evidence that the AA genotype of the c.834+7G>A Gas6 polymorphism may have a protective role against acute coronary syndrome (ACS) (Jiang et al 2009). In addition, elevated levels of Gas6 protein are associated with a variety of disease states, including venous thromboembolic disease, systemic lupus erythematosus, chronic renal failure, and preeclampsia (Dihingia et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, GAS6 levels are reported to be significantly lower in patients with undergoing CABG than controls [35]. Jiang et al [36] reports that the median plasma GAS6 levels are significantly lower in patients with acute coronary syndrome than healthy controls. GAS6 is highly expressed by endothelial cells in atherosclerosis-prone areas of the vascular tree.…”
Section: Discussionmentioning
confidence: 90%
“…7 A single nucleotide polymorphism (c.834 + 7G4A) of this gene in intron 8 was demonstrated to be protective against stroke, diabetes and acute coronary syndrome. 4,8,9 We suggest that GAS6 intron 8 c.834 + 7G4A gene polymorphism might be a risk factor for diabetic nephropathy in type 2 diabetic individuals. In this study, we compared frequency of GAS6 intron 8 c.834 + 7G4A gene polymorphism between non-diabetic individuals and type 2 diabetic patients with diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 84%
“…8 This genotype was also found to be protective from type 2 diabetes as well as acute coronary syndrome and stroke. 4,8,9 It was shown that fasting glucose, TNF-alpha, interleukin-6 and vascular cell adhesion molecule-1 levels decrease when GAS6 protein plasma concentration increases. That means GAS6 is related to diabetes, inflammation and endothelial function.…”
Section: Discussionmentioning
confidence: 99%